Interaction of Maternal Separation on the UCh Rat Cerebellum - Oliveira, S. A. [UNESP]; Fontanelli, B. A. F. [UNESP]; Stefanini, M. A.; Chuffa, L. G. A. [UNESP]; Teixeira, G. R. [UNESP]; Lizarte, F. S. N.; Tirapelli, L. F.; Quitete, V. H. A.; Matheus, S. M. M. [UNESP]; Padovani, C. R. [UNESP]; Martinez, M.; Martinez, F. E. [UNESP] (Wiley-Blackwell, 2014)
Maternal care is the main source of signals and stimuli for proper development, growth, and production of adjustment responses to stressful factors. Adverse experiences in childhood are associated with a vulnerability to developing abusive ethanol ingestion via alterations of the response of the hypothalamic-pituitary-adrenal axis. Alcoholism causes global brain abnormalities, with the cerebellum being one of the most susceptible areas. We evaluated the effect of maternal separation on the cerebellum structure of male UCh rats. Adult male UChA (low 10% ethanol consumption) and UChB (high 10% ethanol consumption) rats were divided in to four experimental groups: (1) UChA, (2) UChA maternal separation (MS), (3) UChB, and (4) UChB MS. The MS occurred between the 4th and 14th days of age, for 240 min day(-1). Euthanasia was performed at 120 days of age. An image analysis system was used to measure cerebellar cortical height and Purkinje cellular area and height in five rats from each group. The cerebellar sections were stained with antibodies against IGFR-I. MS did not alter the ethanol consumption of UChA and UChB rats. Corticosterone level was significantly higher in UChA MS and UChB MS rats than in UChA and UChB rats. The Purkinje cellular area and height were higher in UChA MS rats. IGFR-I expression was observed in the cortical glomerular area of UChA MS and UChB MS rats. MS altered the Purkinje cells in the cerebella of male UCh rats. Microsc. Res. Tech. 77:44-51, 2014. (c) 2013 Wiley Periodicals, Inc.
Keywords: maternal separation; cerebellum; UCh rat